Screening of Lynch syndrome in endometrial cancer in Iranian population with mismatch repair protein by immunohistochemistry - Somayyeh Noei Teymoordash; Maliheh Arab; Massih Bahar; Abdolali Ebrahimi; Maryam Sadat Hosseini; Farah Farzaneh; Tahereh Ashrafganjoei (Babol University of Medical Sciences, 2022)
Background: Lynch syndrome (LS) is one of the commonest genetic cancer syndromes, with an incidence rate of 1 per 250-1000 population. The aim of this study was to evaluate the frequency and characteristics of MMR deficiency in endometrial cancer in Iranian women. Methods: One hundred endometrial carcinoma cases who referred to the gynecological oncology clinic of Imam Hossein Medical Center located in Tehran, Iran, from 2018 to 2020 were included in the study. Immunohistochemistry (IHC) evaluation was performed mainly on the hysterectomy specimens of all endometrial cancer (EC) patients to assess MMR proteins (MLH1, MSH2, MSH6, and PMS2) expression. Results: A total of 23 out of 100 (23%) cases were identified through IHC screening to be MMR-deficient. The most common types were loss of MLH1/PMS2 (17.4%) and solitary MSH2 (17.4%) expressions followed by PMS2/MSH2 loss (13%). MMR deficiency (dMMR) histopathology was significantly overrepresented in patients with family history of cancer or Lynch syndrome (LS) associated cancers (p-values of 0.016 and 0.005, respectively). The rate of myometrial invasion and lower uterine segment involvement were also significantly higher in dMMR EC patients compared to MMR-intact EC (p-value of 0.021 and 0.018, respectively). Conclusion: MMR deficiency, observed in 23% of endometrial cancer cases, was associated with higher rates of poor prognostic factors including myometrial invasion and lower uterine segment involvement. The presence of positive family history of cancer and family history of LS-associated cancer increased the probability of MMR-deficiency in endometrioid endometrial cancer to 47% and 70%, respectively